USE OF SLIDES IN ACCOUNTING INSTRUCTION. - Fleig, W. J. (The Accounting Review, 1948)
Abstract The article presents the use of slides in accounting instructions. During 1937 Accounting Department at the Ohio State University, purchased a 3X4 slide projector. Most of the slides consisted of solutions to problems and were used in classes which could be scheduled to meet in the room equipped for projection. It is not necessary to prepare separate copy for each slide in a step-by-step series. All of the slides in the worksheet series were prepared from a single copy of the complete illustration. This was accomplished by blocking out portions of the copy with white paper. The projector can be adapted for use in various size classrooms by means of lenses of different focal lengths. This type of machine because its fan is noisy, can he used more effectively if it is placed behind the students. The fan is necessary because of the high wattage of the lamp required to permit projection in a lighted room. Any type of white surface is suitable for use as a screen for black and white projection.